INTERNALISASI NILAI KARAKTER ISLAM OLEH ORGANISASI DIVISI PENDIDIKAN DALAM MENINGKATKAN BUDAYA RELIGIUS DI PONDOK PESANTREN PUTRI NURUL ULUM BLITAR - Yazid Nur Mahendra; Ika Ratih Sulistiani; Muhammad Fahmi Hidayatullah (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Social skills in today's era began to fade with due to the rapid development of technology, this cannot be done it is undeniable seeing the times that continue to evolve from from age to age from year to year. Technology is like a knife double-edged, if used properly then the output will be good on the other hand, if it is bad, it will be bad. In this case the role of a teacher aqidah akhlak's role is very much needed, which aqidah akhlak's teachers other than good role model as well as a qualified moral workshop. Therefore learning aqidah morals also becomes a point of view by relation to belief and morality. Aqidah and akhlak learning become a stepping stone to improve social skills children who have been eroded by time. The role of the aqidah akhlak teacher in improve social skills through a scientific approach requires research first, on the learning model model with the aim of seeing the relationship between the suitability of the learning model used with the subjects of aqidah akhlak and social skills. The second is the learning strategy, this relates to what steps will the teacher take in the process learning aqidah akhlak and in improving skills social. The third, the implementation of learning which in implementation of learning can be seen whether the teacher can improve social skills through a scientific approach.